Analysis of Green Land Changes to Building Land Using Geographic Information System (GIS) in Salatiga City from 2013 to 2019 - Riska Vennithasari; Frederik Samuel Papilaya (Politeknik Negeri Batam, 2020)
The land is a crucial element in human life as space and resource. The development of a region will not be neglected by the use of land. Data from BPS Salatiga 2013 to 2019 shows an average increase in population reaching 1.45%. Land-use changes in a region will affect the geographical conditions of the region itself. Therefore, the latest information is needed in order to anticipate continuous changes. The research was conducted in Salatiga and the time of the study starts in August 2019 until January 2020. The purpose of this research is to see and analyze the extent of each transformation of the land use and land cover changes by utilizing Landsat 8 Satellite Imagery in 2013-2019. Data processing in this study uses spatial analysis overlay technique that combined with unsupervised classification and confusion matrix method through SAGA GIS software. The results of data processing will afford new maps and land use change tables then explained descriptively. Based on the analysis that has been done, In 2013, the land use in Salatiga was dominated by green land of 3.031,29 ha which was then followed by land use for built-up land reaching 2.033,91 ha. And in 2019, land use was still dominated by green land of 2.499,03 ha which was then followed by the use of built-up land of 2.483,64 ha. The final result of the area of Salatiga in 2013 - 2019 which experiencing land change from a green land to be built up land is 755,91 hectares.